Natural History of Branch-Duct Intraductal Papillary Mucinous Neoplasms of the Pancreas: A Case Report - Casadei, Riccardo; Ricci, Claudio; D’Ambra, Marielda; Taffurelli, Giovanni; Zingaretti, Caterina C; Pacilio, Carlo A; Calculli, Lucia; Pagano, Nico; Minni, Francesco (JOP. Journal of the Pancreas, 2014)
Context The natural history of incidental branch-duct intraductal papillary mucinous neoplasm of the pancreas is still unknown. Case report The case of a 74-year-old man who had been diagnosed 14 years previously with an incidental branch-duct intraductal papillary mucinous neoplasm of the pancreatic head, 30 mm in size, without mural nodules and dilatation of the main pancreatic duct is herein reported. After an exploratory laparotomy at the time of diagnosis (when he was 60 year-old), the patient was enrolled in a surveillance program. Fourteen years after the diagnosis, the cystic lesion showed an increase in size, Wirsung duct dilatation and the presence of several mural nodules. A total pancreatectomy was performed and a diagnosis of mixed-intraductal papillary mucinous neoplasm diffused throughout the entire pancreas with high grade dysplasia, and a micro-invasive carcinoma (<1 mm) of the pancreatic head was reached. Conclusion The present case confirmed that the natural history of branch-duct intraductal papillary mucinous neoplasms is unpredictable. Thus, an appropriate surveillance program is required for prompt identification of the signs predictive of a malignant transformation of branch-duct intraductal papillary mucinous neoplasms. In high-volume centers, surgery should seriously be considered in young patients who are fit for surgery. Image: MRI plus cholangiopancreatography.